If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -18 = 12x + 28 Reorder the terms: -18 + 10x = 12x + 28 Reorder the terms: -18 + 10x = 28 + 12x Solving -18 + 10x = 28 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -18 + 10x + -12x = 28 + 12x + -12x Combine like terms: 10x + -12x = -2x -18 + -2x = 28 + 12x + -12x Combine like terms: 12x + -12x = 0 -18 + -2x = 28 + 0 -18 + -2x = 28 Add '18' to each side of the equation. -18 + 18 + -2x = 28 + 18 Combine like terms: -18 + 18 = 0 0 + -2x = 28 + 18 -2x = 28 + 18 Combine like terms: 28 + 18 = 46 -2x = 46 Divide each side by '-2'. x = -23 Simplifying x = -23
| -3+2y=-8 | | 6-m=-11 | | 3*x^2-85*x-79=0 | | 3*x^2-85*x-316=0 | | (2x+10)(3x-4)=0 | | 3*x^2-91*x-316=0 | | 5+3(x+4)+2x=6(x-3)+5 | | A=288pir^2(7) | | A=288pir^27 | | 10+3(4x-6)+7=35 | | 17+5x=6x-13 | | -30*a^14*b^8/10*a^17*b^-5= | | 3(3x-4)-5=2(2-x) | | 21x^2=-11x+40 | | 293=4(x)+3 | | 3/48=(1/2)n | | 7(x+2)-3x-1=6(x+4)-4x+3 | | 36x^2+x-117=0 | | 4(3.75)-5(2.5)=4 | | 4+5y=-2y+18 | | 2x-3-4x=5 | | x^2+x=x^2-2x+6 | | (4/6)x=(5/6)y | | (4/6)x(5/6)y | | (X-3)(2x+9)=9(3x+2) | | y-10=9y-6 | | ml=7.3l | | 9w=2*9w | | 4cosx-2=cosx | | 2^-1=1/64 | | 9x^2-9x-15=0 | | 6+2x+3y=48 |